Dimensions of Students Learning Styles at The University with The Kolb Learning Model - A. Muhammad Idkhan; Muhammad Maruf Idris (International Journal of Environment, Engineering and Education, 2021)
Someone will learn better if the person concerned understands his character in learning. Individuals in learning have various ways; some learn by listening, some learn by reading, and some learn by discovering. These diverse ways of learning by students are known as learning styles. Kolb's learning style is divided into four types, namely converge, assimilator, diverge, accommodator. The purpose of the study was to determine the profile of student learning styles of the Faculty of Engineering, Universitas Negeri Makassar, which is divided into 9 (nine) study programs. Samples taken with an error rate of 5 percent were 177 students. Purposive sampling is used as a sampling technique with special considerations so that it is feasible to be used as a sample. The research measures four types of learning styles, namely Active Experimentation (AE), Concrete Experience (CE), Reflective Observation (RO), and Abstract Conceptual (AC). The results showed that the accommodator learning style was more dominant in students. Of the eight majors that became the research subjects, seven tended to the accommodator learning style, and only one tended to the assimilator learning style. The accommodator learning style combines the poles of active experimentation (doing) and concrete experience (feeling). The use of learning methods following the learning style is Problem-Based Learning which involves all students in the learning process.